English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-18 04:56:52 · 4 answers · asked by alasia s 1 in Science & Mathematics Mathematics

4 answers

without brackets, it will be like this

5x + 3/3i - x - 1/2x
= 4x + 1/ i - 1/2x


with brackets, it turns out different

5x + (3/3)i - x - (1/2)x
= 5x + i - x- (1/2)x
= 10x + 2i - 2x - x
= 7x + 2i

2007-01-18 05:04:14 · answer #1 · answered by wind_liao 2 · 0 0

= 5x -i -x-1/2 x ==7/2*(x) -i
Explanat. 3/3i =1/i = i/i^2=-i

2007-01-18 13:23:48 · answer #2 · answered by santmann2002 7 · 0 0

assuming that ur problem is 5x +(3/3)i - x - (1/2)x.......
5x + i - x - (1/2)x
(7/2)x + i

2007-01-18 13:00:22 · answer #3 · answered by smawtadanyew 2 · 0 0

Brackets and spaces are your friends...

2007-01-18 13:06:38 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers